Dynamic mechanical relaxation behavior of TiZrHfCu-Ni/Be/NiBe high-entropy metallic glasses. (June 2023) - Chen, C.J.; Xu, R.; Yin, B.J.; He, Y.Z.; Zhang, J.Y.; Zhang, P.; Shen, B.L.
Abstract: The dynamic mechanical relaxation processes of metallic glasses are crucial for understanding the glass transition phenomenon, plastic deformation and relaxation mechanism of metallic glasses. In this study, the dynamic mechanical relaxation behaviors of TiZrHfCuNi, TiZrHfCuBe, TiZrHfCuNiBe, and high-entropy metallic glasses (HE-MGs) and conventional Ti13.8 Zr41.2 Cu12.5 Ni10 Be22.5 (Vit1) metallic glass (MG) with different glass-forming abilities (GFA) were investigated by dynamic mechanical analysis. α relaxation was observed in the TiZrHfCuBe and TiZrHfCuNiBe HE-MGs and Vit1 MG. The intrinsic activation energies E α for HE-MGs are obviously higher than that of conventional Vit1 MG. The TiZrHfCuNi HE-MG with the lowest GFA exhibits an abnormally broad peak in the E ′′/ E u curve, which is due to the crystallization. The temperature and frequency dependence of the dynamic mechanical properties was carefully discussed in light of both the Kohlrausch-Williams-Watt (KWW) and quasi-point defects (QPD) models, which indicated different dynamic heterogeneities and defect concentrations in the four MGs. The smaller β KWW value of the HE-MGs compared with the conventional Vit1 MG indicates that the HE-MGs possess a wider characteristic time distribution and larger dynamic heterogeneity. The QPD model matched the experimental data well, and the temperature-dependent correlation factor χ was deduced in the three HE-MGs and Vit1 MG. The χ values of the three HE-MGs are much smaller than that of Vit1 MG, which indicates that the defect concentration and atomic mobility in HE-MGs are lower than those in conventional metallic glasses. This study reveals the dynamic mechanical relaxation behavior in high-entropy metallic glasses, which will enhance our understanding of the mechanical relaxation mechanism and intrinsic characteristics of HE-MGs. Highlights: Dynamic mechanical behaviors of high-entropy metallic glasses were probed by DMA. Dynamic mechanical spectra of HE-MGs can be well described by the KWW and QPD theory. The abnormally broad peak in the E ′′/ E u curve of TiZrHfCuNi HE-MG is due to crystallization process. Intrinsic activation energies E α for HE-MGs are much higher than that of conventional Vit1 MG.